1905 Ind. Stat. Ann. 231, § 2094 - (:unkn) unknown (My University, 1905)
Ch. 5, art. 4, § 2094: Prohibited the concealed carry of any dirk, pistol, Bowie-knife, dagger, sword-cane, or any other dangerous or deadly weapon. Also prohibited the open carry of the same with intent to injure another. Violators punished by destruction of the weapon. Repeat offenders sentence to not more than one year in prison upon third offense.
Keywords: CARRY; CARRY - CONCEALED